Vital Program of Prevention and Treatment of Old Age as a Set of Chronic Diseases in the Conditions of Antibiotic Crisis - Roslyak, Serhiy (British Journal of Healthcare and Medical Research, 2026)
Synonyms are often used for the word old age: wear and tear, infirm old age, weakness, and rarely - the golden autumn of life, maturity. Each period corresponds to its own level of physiological and psychological indicators of the body, and, just as importantly, its own level of comfort, quality of life. Unfortunately, the transition to the next age group is accompanied by a deterioration of these indicators, a violation and loss of important body functions. There is no single theory of old age that most scientists would accept. The latest discoveries of molecular biology, fundamental immunology, bioinformatics and genetics show that the theory of age-related inflammatory processes is the most complete today. According to her, during aging, chronic mild inflammation develops, which causes diseases and geriatric syndromes. An increase in the proportion of senescent cells leads to local and systemic inflammation, to pathological aging with a higher risk of diseases and the quality of life, which deteriorates, reducing its duration. Elevated levels of inflammation are present in the elderly even without infection or injury and lead to the development of metabolic disorders and age-related diseases. We believe that one of the main causes of aging that can be successfully combated is the presence of chronic diseases, polymorbidity of pathological conditions (the presence of two or more chronic diseases that coincide in time in one patient) and complications with long-term use of medicines. The purpose of the work is to develop a program for the prevention and treatment of premature aging, transferring it to a physiological state that is not burdened by diseases; ensuring a normal level of quality in old age, preventing relapses of diseases, increasing functional activity, ensuring a comfortable physical and mental state of a person. The main idea of the proposed therapy is to prevent the changes underlying the development of age-related pathology, to eliminate damage from accumulated damage, that is, to treat old age as a complex of chronic diseases. The material basis of this is the use of propolis, royal jelly, wax moth, zabrus - natural medicines. The obtained results indicate that the developed drugs provide a therapeutic effect where other means have been used without success, and recovery occurs earlier and in the absence of toxicity and side effects. And, most importantly, they do not cause the development of resistance to their influence. Although this study has many strengths (high efficiency, low budget of drugs, their availability, the possibility of parallel use of pharmaceutical drugs, lack of complications), there are both objective and subjective limitations. The objective ones include: an allergic reaction to beekeeping products in approximately 5-7% of the population and a limited scope of clinical research. To the subjective: in medicine - effective prevention of diseases will significantly reduce the amount of pharmacological drugs and services sold, in industry - it is technologically difficult to put the proposed products on the assembly line, that is, to achieve their high profitability. And, most importantly, these are people, most of whom hopes for a magic pill or a "corner", does not understand and does not want to understand that the rescue of a drowning person is the work of the drowning person himself. Therefore, this work is addressed to people who understand and accept full responsibility for their own health and the health of their loved ones.